Preparation method of alkaline electrolyzed water bifunctional catalyst CuS-MOOH

By coating CoOOH on the surface of CuS, CuS@CoOOH composite material is formed, and the HER/OER catalytic reaction is regulated using its crystalline-amorphous interface, the problem of slow reaction kinetics in water cracking technology is solved, and efficient catalytic performance is achieved and cost-reducing effects.

CN119433607APending Publication Date: 2025-02-14HEILONGJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411682304.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the existing water cracking technology, the reaction kinetics of cathode hydrogen evolution reaction (HER) and anode oxygen evolution reaction (OER) are slow, resulting in large energy losses, hindering the application of water cracking technology in actual production.

Method used

By coating metal hydroxyoxide (CoOOH) on the surface of CuS, a CuS@CoOOH composite material is formed, and the HER/OER catalytic reaction is regulated using its crystalline-amorphous interface to improve catalytic activity and stability.

Benefits of technology

It achieves efficient HER/OER catalytic performance, which is better than commercial catalysts Pt/C and Ru2O, reduces the catalyst production cost, and provides a theoretical basis for the large-scale production application of alkaline dual-function electrolytic cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433607A_ABST
    Figure CN119433607A_ABST
Patent Text Reader

Abstract

In view of the defects of low water electrolysis performance (such as low catalytic activity, poor stability, high cost and the like) at present, a novel multi-step wet chemical method is adopted to prepare a CuS (at) MOOH (M: transition metal) electrocatalyst containing a crystal-amorphous interface to solve the problems. According to the catalyst, an alkaline bifunctional electrolytic tank with high catalytic activity and good stability is successfully prepared through a simple preparation process and low manufacturing cost. Under the action of a crystal-amorphous interface, the CuS (at) MOOH can cause electrons of orbits of metal active sites to exert a better redistribution function, rapid transfer of the electrons is promoted, and meanwhile, the adsorption energy of Cu and M bimetallic active sites to reaction intermediates in HER and OER reactions is reduced. Wherein the CuS (at) CoOOH has an overpotential of hydrogen evolution of 38 mV (HER) and oxygen evolution of 190 mV (OER) by taking Co as an example. According to the water electrolysis device taking CuS-coated CoOOH as a cathode and an anode, ultrahigh electrolysis efficiency is maintained in a continuous electrolysis state of 100 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a CuS@MOOH bifunctional electrocatalyst composite material containing a crystalline-amorphous interface and application of the same to a water electrolysis device. Background Art

[0002] At present, the use of electrochemical water splitting to generate clean energy can help the development of a fossil-free energy system worldwide [1]. However, due to the slow reaction kinetics of the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER) of water splitting, huge energy losses are caused, which in turn hinders the application of water splitting technology in practical production. Therefore, it is urgent to develop electrocatalysts that can drive the HER and OER bifunctional catalysis at low potential.

[0003] Currently, designing the crystalline phase-amorphous phase interface in HER / OER catalysts is gradually being explored as a promising path [2]. The crystalline phase structure has good conductivity and structural stability [3]. The amorphous phase structure has the typical characteristics of "long-range disorder and short-range order", which gives it abundant active sites, defects and unsaturated electronic configurations, thus showing excellent electrocatalytic performance.

[0004] During the HER electrocatalytic process, the electrical properties of the catalyst surface have a great influence on the adsorption energy between the metal site and the reaction intermediate *H[4]. CuS is a common electronegative material with good electrocatalytic activity and stability[5]. However, the Cu in CuS has a +2 valence. Since the electrons in its outermost 3d orbital are in a half-filled state, it is not easy for the adsorption site of the active intermediate to capture protons. Therefore, finding a method to reduce the valence of Cu in CuS so that the 3d orbital is filled is a shortcut. Metal oxyhydroxide (MOOH) has a high-valence metal and its electrons are easily excited. The unpaired electrons in the excited metal can attract oxygen-containing intermediates with electrons (*OH, *O, *OOH) to solve the problem of slow OER kinetics. Metal oxyhydroxide (MOOH) has a high-valence metal and its electrons are easily excited. The unpaired electrons in the excited metal can attract oxygen-containing intermediates with electrons (*OH, *O, *OOH) to solve the problem of slow OER kinetics. Taking Co as an example among transition metal elements, we successfully coated the surface of crystalline CuS with metal hydroxide oxide (CoOOH) using a controllable liquid phase reaction, which showed a structure with an internal cavity of about 400 nm covered with layered nanosheets. In this structure, CuS provides a stable support for MOOH, effectively avoiding the agglomeration phenomenon that is very easy to occur during the electrocatalytic process. Importantly, thanks to the rapid electron transfer ability and orbital electron redistribution ability between crystalline CuS and amorphous MOOH, this can effectively enhance the HER / OER performance of CuS@CoOOH. Summary of the invention

[0005] In view of the problems of low electrolysis efficiency, poor electron transfer ability and high cost in current alkaline electrolytic cells, the present invention provides a preparation method and application of a CuS@CoOOH composite material for an alkaline electrolytic cell bifunctional catalyst.

[0006] The present invention discloses a preparation method and application of a CuS@CoOOH composite material for an alkaline electrolytic cell bifunctional catalyst, wherein the preparation method of the composite material for a bifunctional alkaline electrolytic cell is achieved by the following steps: 1. A method for preparing a composite electrolytic cell bifunctional catalyst having an alkaline internal cavity structure of CuS covered with CoOOH layered nanosheets, characterized in that the preparation of the alkaline electrolytic cell bifunctional material is achieved by the following steps: 2. The preparation method of the composite material composed of three-dimensional hollow CuS nanocubes and two-dimensional CoOOH nanosheets as described in step 1 is carried out according to the following steps: 1) Weigh copper sulfate and trisodium citrate as raw materials, with a mass ratio of copper sulfate to trisodium citrate of (1-3):1. Dissolve the weighed raw materials in deionized water (60-100) mL and stir evenly. Then add sodium hydroxide solution (1.2 mol / L) (10-30) mL and ascorbic acid solution (0.03 mol / L) (40-60) mL, stir for 3 min, age for 1 h, collect the precipitate by centrifugation with deionized water and ethanol, and dry the precipitate in a vacuum drying oven to obtain a Cu2O precursor. 2) Dissolve the solid powder obtained in step 1 in deionized water (60-100) mL, add sodium sulfide aqueous solution (6.25 mM) (30-50) mL for sulfidation, stir for 30 min, and then add sodium thiosulfate (1.0 M) (5-15) mL for etching for 30 min; 3) The liquid obtained in step 2 is centrifuged with deionized water and ethanol to collect the precipitate, and the precipitate is placed in a vacuum drying oven for drying to obtain a CuS precursor; 4) Dissolve the CuS precursor obtained in step 3 with cobalt nitrate (0.5 M), trisodium citrate and hexamethylenetetramine in a mass ratio of 1:(1-5) in (40-60) mL of deionized water, stir for 0.5-3.5 h, collect the precipitate by centrifugation with deionized water and ethanol, and dry the precipitate in a vacuum drying oven to obtain a composite material of CuS with an internal cavity coated with two-dimensional layered nanosheets MOOH; 3. The method for preparing a composite material of CuS with an internal cavity and coated with two-dimensional layered nanosheet CoOOH according to step 2 is characterized in that: the drying method in steps 1, 3 and 4 is: drying at 60-90 °C for 12-24 h; 4. As described in step 1, the use of the composite material of the internal cavity CuS covered with CoOOH layered nanosheets is characterized in that: the process is carried out according to the following steps: the composite material of the two-dimensional nanosheet CoOOH assembled with the three-dimensional cavity structure CuS nanoflower is used as an electrochemical catalytic material to prepare a catalytic element, and the prepared catalytic element is placed under the conditions of a temperature of 15-35 ° C and 1M KOH for detection; 5. According to step 4, the application of the composite material of CuS with internal cavity covered with CoOOH layered nanosheets is characterized in that: the method for preparing the catalytic element is: ultrasonically disperse the CuS nanocube composite material of the two-dimensional nanosheet CoOOH assembled three-dimensional cavity structure in 1-10 times the volume of ethanol solution, add 30 microliters of naphthol solution, and obtain a uniformly dispersed suspension. Cut the nickel foam substrate into a 1cm*1cm square. Then apply the suspension on the nickel foam electrode cleaned with hydrochloric acid and acetone, and dry it at 50-90°C for 2-5 hours to obtain an electrocatalytic element.

[0007] Compared with the prior art, the advantages of the present invention are: (1) The CuS@CoOOH alkaline bifunctional electrolytic cell catalyst material prepared by the method of the present invention uses CuS with HER catalytic potential and CoOOH with OER catalytic potential as basic materials for compounding to obtain a composite material with good conductivity, stability and high catalytic activity; (2) The CuS@CoOOH alkaline bifunctional electrolytic cell catalyst material prepared by the method of the present invention is obtained only through a multi-step liquid phase reaction, which reduces energy consumption and saves costs.

[0008] (3) The CuS@CoOOH alkaline bifunctional electrolytic cell catalyst material prepared by the method of the present invention achieves high HER / OER performance by regulating the HER / OER catalytic reaction at the crystalline-amorphous interface, thereby obtaining power generation performance that is superior to that of currently commercial precious metal catalysts such as Pt / C and Ru2O, effectively reducing the catalyst production cost and providing a theoretical basis for the large-scale production and application of alkaline bifunctional electrolytic cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 TEM image (a) and SEM image (b) of Cu2O. Figure 2 TEM image (a) and SEM image (b) of CuS. Figure 3TEM image (a) and SEM image (b) of CuS@CoOOH. Figure 4 The contact angle diagram of CuS@CoOOH and electrolyte 1M KOH; Figure 5 XRD pattern of Cu2O (a); XRD pattern of CuS (b); Figure 6 is the XRD pattern of CuS@CoOOH; Figure 7 HER performance diagram of CuS@CoOOH and Pt / C (a); OER performance diagram of CuS@CoOOH and Ru2O (b); Figure 8 Schematic diagram of the stability of CuS@CoOOH with Pt / C and Ru2O by chronoamperometry; The beneficial effects of the present invention are verified by the following examples DETAILED DESCRIPTION

[0010] Preparation of CuS@CoOOH catalyst ① Dissolve 375 mg of copper sulfate and 147 mg of trisodium citrate in 80 ml of deionized water and stir evenly. ② Add 20 ml of NaOH solution (1.2 mol / L), then add 50 ml of ascorbic acid solution (0.03 mol / L), stir for 3 min, precipitate for one hour, and collect by centrifugation to obtain cuprous oxide nanocubes. ③ Introduce 40 ml of sodium sulfide aqueous solution (6.25 mM) into the suspension of cuprous oxide (100 mg) and deionized water (60 ml) for sulfidation, stir for 30 min, then centrifuge and collect the sample. ④ Disperse the sample of step ③ in 20 ml deionized water and 20 ml ethanol, add sodium thiosulfate (16 ml 1.0 M) and etch for 30 min, centrifuge, wash the product with deionized water and ethanol respectively, and dry the product in a 60 ℃ oven for 12 hours; ⑤ Put the copper sulfide sample of step ④, trisodium citrate (0.236 g), cobalt nitrate (0.432 g), and hexamethylenetetramine (0.202 g) in 230 ml deionized water and ultrasonically dissolve for 10 min; put the solution into a 250 ml volumetric flask and oil bath at 85 ℃ for 5 h; ⑥ Wash the product of step ⑤ with deionized water and ethanol respectively, and dry the product in a 60 ℃ oven for 12 hours to obtain an electrocatalyst material.

[0011] (2) Preparation of CuS@CoOOH electrode: All electrochemical measurements were performed on a Chenhua electrochemical workstation (CHI 760E, Shanghai) in 1 M KOH electrolyte using a three-electrode setup. Hg / HgO electrode and graphite rod were used as reference electrode and counter electrode, respectively. 5 mg of CuS@CoOOH, 1 mg of carbon black and 30 uL of Nafion (5 wt%) were dispersed in 40 uL of a mixture of water and ethanol (v: v = 1:1) and treated under ultrasound for 30 min to form a uniform ink. The catalyst ink was then applied to a Ni foam (1 cm × 1 cm) substrate to make a working electrode. The nickel foam was pretreated by soaking it in acetone for 24 h to remove organic impurities on the surface, followed by multiple rinses with water and ethanol.

[0012] The catalytic materials of the first embodiment and the corresponding characterization and performance analysis: Figure 1 a and 1b are the SEM and TEM images of Cu2O. Figure 1 In a, we can observe that Cu2O is a smooth-surfaced cube with a diameter of about 300-400 nm. Figure 1 The low-magnification SEM image in b proves that the size of the Cu2O synthesized by us is similar and uniform; Figure 2 a and 2b are SEM and TEM images of CuS. Figure 2 In a, we can observe that CuS is a cube with a cavity structure, with a diameter of about 300-400 nm. Figure 1 The low-magnification SEM image in b proves that the size of the CuS synthesized by us is similar and uniform; Figure 3 a and 3b are the SEM and TEM images of CuS@CoOOH. Figure 3 In a, we can observe that CuS@CoOOH is surrounded by a layer of dense two-dimensional CoOOH nanosheets with a diameter of about 400-600 nm, while retaining the original CuS cavity structure. Figure 1 The low-magnification SEM image in b proves that the sizes of the CuS@CoOOH synthesized by us are similar and uniform; Figure 4 This is the contact angle of the CuS@CoOOH catalyst with 1M KOH. It can be directly observed that the contact angle of CuS@CoOOH is 15.9°, which is a hydrophilic material with high surface energy. This proves that the CuS@CoOOH catalyst we synthesized is easily penetrated when in contact with the electrolyte solution, increasing the contact between the catalyst and the electrolyte solution; Figure 5 a and 5b are the XRD patterns of CuS and Cu2O. Figure 5In a, we can observe that the XRD peak of CuS is consistent with the standard card of CuS (JCPDS 06-0464), which proves the successful synthesis of copper sulfide. Figure 5 In b, we can observe that the XRD peak of Cu2O is consistent with the standard card of Cu2O (JCPDS 78-2076), which proves the successful synthesis of cuprous oxide; Figure 6 is the XRD pattern of CuS@CoOOH, Figure 6 We can observe that the XRD peaks of CuS@CoOOH have obvious amorphous characteristics, and all XRD peaks disappear. This not only proves that CoOOH is amorphous, but also shows that there is a crystalline-amorphous interface between crystalline CuS and amorphous CoOOH; Figure 7 a is the HER performance diagram of CuS@CoOOH catalyst and commercial catalyst Pt / C. Figure 7 b is the OER performance diagram of CuS@CoOOH catalyst and commercial catalyst Ru2O. Figure 7 As can be seen in a, CuS@CoOOH only needs an overpotential of 38 mV to reach 10 mA cm -2 The current density is outstanding among the reported copper-based materials. This is because CuS itself has electronegativity. After being coated with CoOOH, CuS@CoOOH has higher electronegativity, which optimizes the adsorption of *H at the Cu site and significantly improves the HER performance. Figure 7 As can be seen in b, CuS@CoOOH only needs an overpotential of 190 mV to reach 10 mA cm -2 The current density is 2.34 Å, which is due to the presence of the crystalline-amorphous interface, which can activate more edge Co active sites and cause orbital electron rearrangement of Co, optimize the binding energy of O intermediates, and thus improve the OER catalytic performance in the water electrolysis process. Figure 8 The chronoamperometric curves of CuS@CoOOH catalyst as cathode and anode for water electrolysis and commercial catalysts Pt / C and Ru2O as cathode and anode for water electrolysis. It can be seen from the figure that the decomposition efficiency of CuS@CoOOH catalyst as cathode and anode has not significantly weakened after 100 hours of continuous water electrolysis. However, the traditional commercial catalyst has shown obvious weakening, which further proves that CuS@CoOOH-6 has the potential to be put into actual water electrolysis production.

[0013] References [1] L. Quan, H. Jiang, G. Mei, Y. Sun, B. You, Chem. Rev. 2024, 124,3694-3812. https: / / doi.org / 10.1021 / acs.chemrev.3c00332 [2] Y. Sui, X. Ji, Chem. Rev. 2021, 121, 6654-6695. https: / / doi.org / 10.1021 / acs.chemrev.1c00191 [3] H. Ding, H. Liu, W. Chu, C. Wu, Y. Xie, Chem. Rev. 2021, 121,13174-13212. https: / / doi.org / 10.1021 / acs.chemrev.1c00234 [4] X. Li, L. Xiao, L. Zhou, Q. Xu, J. Weng, J. Xu, B. Liu, Angew. Chem. Int. Edit. 2020, 59, 21106-21113. https: / / doi.org / 10.1002 / anie.202008514 [5] Y. Zhang, F. Gao, D. Wang, Z. Li, X. Wang, C. Wang, K. Zhang, Y. Du, Coordin. Chem. Rev. 2023, 475, 214916; https: / / doi.org / 10.1016 / j.ccr.2022.2149.

Claims

1. A method for preparing a composite electrolytic cell bifunctional catalyst in which CuS with an alkaline internal cavity structure is covered with MOOH layered nanosheets, characterized in that The preparation of the bifunctional material for alkaline electrolytic cell is achieved through the following steps.

2. The method for preparing the composite material composed of three-dimensional hollow CuS nanocubes and two-dimensional nanosheets MOOH as claimed in claim 1 is carried out by the following steps: 1) Weigh copper sulfate and trisodium citrate as raw materials, with a mass ratio of copper sulfate to trisodium citrate of (1-3):

1. Dissolve the weighed raw materials in deionized water (60-100) mL and stir evenly. Then add sodium hydroxide solution (1.2 mol / L) (10-30) mL and ascorbic acid solution (0.03 mol / L) (40-60) mL, stir for 3 min, age for 1 h, collect the precipitate by centrifugation with deionized water and ethanol, and dry the precipitate in a vacuum drying oven to obtain a Cu2O precursor. 2) Dissolve the solid powder obtained in step 1 in deionized water (60-100) mL, add sodium sulfide aqueous solution (6.25 mM) (30-50) mL for sulfidation, stir for 30 min, and then add sodium thiosulfate (1.0 M) (5-15) mL for etching for 30 min; 3) The liquid obtained in step 2 is centrifuged with deionized water and ethanol to collect the precipitate, and the precipitate is placed in a vacuum drying oven for drying to obtain a CuS precursor; 4) Dissolve the CuS precursor obtained in step 3 with transition metal nitrate (0.5 M), trisodium citrate and hexamethylenetetramine in a mass ratio of 1:(1-5) in (40-60) mL of deionized water, stir for 0.5-3.5 h, collect the precipitate by centrifugation with deionized water and ethanol, and dry the precipitate in a vacuum drying oven to obtain a composite material of CuS with an internal cavity coated with two-dimensional layered nanosheets MOOH.

3. The method for preparing the composite material of CuS with internal cavity coated by two-dimensional layered nanosheet MOOH according to claim 2, characterized in that: The drying method described in steps 1, 3 and 4 is: drying at 60-90°C for 12-24 hours.

4. The use of the composite material of CuS with internal cavity covered with MOOH layered nanosheets as claimed in claim 1, characterized in that: The method should be carried out in the following steps: a catalytic element is prepared by assembling a three-dimensional cavity structure CuS nanocube composite material of two-dimensional nanosheet MOOH as an electrochemical catalytic material, and the prepared catalytic element is placed under the conditions of a temperature of 15-35 °C and 1M KOH for detection.

5. The use of the composite material of CuS covered with MOOH layered nanosheets in the internal cavity according to claim 4, characterized in that: The method for preparing the catalytic element is as follows: ultrasonically dispersing a CuS nanocube composite material of a three-dimensional cavity structure assembled from two-dimensional nanosheets MOOH in 1-10 times the volume of an ethanol solution, adding 30 uL of a naphthol solution to obtain a uniformly dispersed suspension, then applying the suspension on a nickel foam electrode cleaned with hydrochloric acid and acetone, and drying it at 50-90°C for 2-5 hours to obtain an electrocatalytic element.